A method and device for enhancing the hardness of carbon materials and application thereof in sodium ion batteries
Through low-temperature, high-pressure plasma excitation and catalyst dehydration treatment, deep oxidation and cross-linking of hard carbon materials, the cycle stability of hard carbon materials in sodium ion batteries is solved, and high hardness and excellent cycle performance are achieved.
Patent Information
- Application Number
- CN202410037655.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-01-10
AI Technical Summary
Hard carbon materials have poor circulation stability in sodium ion batteries, resulting in electrode expansion and interface rupture, affecting energy storage performance, and the existing technology has failed to effectively improve its hardness.
Plasma excitation of oxygen-saturated thermoset polymer under low temperature and high pressure environments, combined with catalyst dehydration treatment, deep oxidation and aromatic structure crosslinking are used to prepare high-hardness carbon materials.
The high hardness improvement of hard carbon materials has been achieved, with Vickers hardness reaching 1.1~2.0GPa, and the circulation performance is significantly better than that of the commercially available hard carbon negative electrode. After 15,000 cycles, it still maintains 80% capacity, solving the shortcomings of hard carbon materials and circulation performance. .
Smart Images

Figure CN117945386B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and more specifically, to a method for enhancing the hardness of carbon materials and the application of the method in sodium ion batteries. Background Art
[0002] As global energy demand continues to grow, the research and development and application of energy storage and power batteries have become increasingly important. Traditional lithium-ion batteries have achieved great success in electric vehicles, renewable energy storage and other fields, but their resource scarcity and environmental impact have attracted people's attention. In this context, sodium-ion batteries, as an emerging alternative technology, have attracted much attention due to their resource advantages.
[0003] Hard carbon materials are the mainstream negative electrode materials for current commercial sodium-ion batteries. Compared with other carbon materials and alloy and conversion negative electrodes, hard carbon negative electrodes have the advantages of high reversible capacity and low voltage, and their reliable source of raw materials can support the long-term and stable operation of the sodium-ion battery industry chain. Sodium-ion batteries have the core advantage of abundant sodium resources and are most suitable for large-scale energy storage. However, their current cycle stability has not yet reached 10,000 cycles, far less than the energy storage demand. Among them, hard carbon is the key to restricting the sodium electric cycle performance. Unlike graphite with few grain boundaries, hard carbon has more and unevenly distributed electrode / electrolyte interfaces due to its abundant grain boundaries and highly active surface chemistry. The larger size of sodium ions will cause greater electrode expansion during the embedding process, which can easily cause interface rupture, resulting in poor cycle performance.
[0004] Therefore, how to enhance the hardness of hard carbon so that it produces a smaller volume expansion when ions are embedded, thereby stabilizing the electrochemical interface, has become an important problem that needs to be solved urgently. Chinese Patent Publication No. CN112158835A discloses a method of increasing the hardness of carbon materials by doping nanodiamonds, and Chinese Patent Publication No. CN113896533A discloses a method of increasing the hardness of carbon materials by high temperature and high pressure treatment of fullerenes, but this method introduces sodium storage inactive components, which will affect the sodium storage capacity. At present, there is no method for increasing the hardness of the intrinsic structure of hard carbon at home and abroad. . Summary of the invention
[0005] The purpose of the present invention is to solve the defects mentioned in the above background technology by proposing a method and device for enhancing the hardness of carbon materials and their application in sodium ion batteries.
[0006] The technical solution adopted by the present invention is as follows:
[0007] In one aspect, the present invention provides a method for increasing the hardness of a carbon material, characterized in that the method comprises the following steps:
[0008] S1, placing a thermosetting polymer in a reaction device, and allowing it to stand in a pure oxygen atmosphere at a low temperature and high pressure environment to obtain an oxygen-saturated thermosetting polymer;
[0009] S2, placing the reaction device used in S1 in a plasma excitation chamber, applying a high-voltage and high-frequency electric field while pumping the reaction device used in S1 into a low-pressure atmosphere to obtain an oxidized thermosetting polymer;
[0010] S3, taking the oxidized thermosetting polymer obtained in S2, placing it in a catalyst solution, soaking and drying it, pre-carbonizing it under a protective atmosphere, acid-washing it, washing it with water to remove impurities, and drying it;
[0011] S4, taking the pre-carbonized product obtained in S3, heating it for a second time for carbonization, and cooling it to obtain a high-hardness carbon material.
[0012] Preferably, the thermosetting polymer in S1 is selected from one or more of phenolic resin, epoxy resin, unsaturated polyester resin, silicone resin, polyurethane, and urea-formaldehyde resin; the particle size volume distribution of the thermosetting polymer is D 50 =10~100μm.
[0013] Preferably, the reaction device used in S1 includes a high-pressure reactor and a low-temperature bath, the thermosetting polymer is placed in the high-pressure reactor, the high-pressure reactor is filled with pure oxygen to a high pressure and then sealed, the high-pressure reactor is placed in a low-temperature bath, and a low-temperature medium is placed in the low-temperature bath, and the low-temperature medium is selected from one or more of liquid oxygen, liquid nitrogen, liquid argon, liquid air, and liquid helium.
[0014] Preferably, the low temperature in S1 is -300 to -100°C;
[0015] Preferably, the high pressure in S1 is 100-1000 kPa;
[0016] Preferably, the standing time in S1 is 0.5-10h;
[0017] Preferably, the gas pressure of the plasma excitation chamber in S2 is 0.001 to 1×10 -7 Pa.
[0018] Preferably, the voltage of the electric field in S2 is 1 to 100 kV, and the frequency is 1 to 10 GHz.
[0019] Preferably, the low pressure atmosphere in S2 is evacuated to 0.001 to 1×10 -7 Pa.
[0020] Preferably, the catalyst solution in S3 is selected from one or more of zinc chloride solution, calcium chloride solution, nickel chloride solution and ferric chloride solution, and the mass fraction of the catalyst solution is 5%-50%.
[0021] Preferably, the impregnation ratio of the catalyst to the oxidative thermosetting polymer in S3 is 0.1 to 5:1.
[0022] Preferably, the protective gas in S3 is selected from one or more of nitrogen, argon and helium.
[0023] Preferably, the pre-carbonization temperature in S3 is 400-900° C., and the pre-carbonization time is 0.5-10 h.
[0024] Preferably, the acid used for pickling in S3 is 0.1 mol / L to 1 mol / L hydrochloric acid, nitric acid or sulfuric acid, and the degree of water washing needs to satisfy the pH value of the filtrate of 5-9.
[0025] Preferably, the carbonization heating rate in S4 is 1-10°C / min, the carbonization temperature is 1000-1700°C, and the carbonization time is 2-10h.
[0026] Preferably, the carbonization method in S4 further comprises:
[0027] During the reaction process of step S4, a hydrocarbon-containing gas is introduced at a flow rate of 0.1-1000 ml / min for surface coating or pore plugging;
[0028] The hydrocarbon-containing gas includes any one or more of natural gas, methane, ethane, acetylene, propyne, benzene, toluene and xylene.
[0029] Preferably, the high hardness carbon material in S4 has a Vickers hardness of 1.1 to 2.0 GPa.
[0030] On the other hand, the present invention provides a device for strengthening the hardness of carbon materials, which is used to implement any of the preparation methods described above, including a low-temperature bath and a high-pressure reactor placed in the low-temperature bath, the low-temperature bath is filled with a low-temperature medium, the high-pressure reactor is sealed by a sealing device, and also includes a vacuum device for regulating the pressure of the high-pressure reactor, and also includes a discharge positive electrode and a discharge negative electrode, the discharge positive electrode and the discharge negative electrode are placed on both sides of the low-temperature bath and the high-pressure reactor as a whole, so that a plasma excitation chamber is formed between the low-temperature bath and the high-pressure reactor.
[0031] In a third aspect, the present invention also provides an application of the high-hardness carbon material according to any one of the above items in the field of negative electrodes of sodium ion batteries.
[0032] The present invention provides a method and device for enhancing the hardness of carbon materials and application thereof in sodium ion batteries.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The present invention hardens the intrinsic structure of the hard carbon active material without introducing inactive components, thus having a higher sodium storage capacity.
[0035] (2) The present invention combines bulk adsorption of oxygen under low temperature conditions with low temperature oxygen plasma technology to deeply oxidize the bulk phase of the precursor, thereby overcoming the shortcoming that conventional plasma technology can only perform surface oxidation treatment.
[0036] (3) The present invention introduces a catalyst to dehydrate the precursor, so that the aromatic structure of the precursor is fully cross-linked, thereby preventing the carbon layer from stacking during the subsequent heat treatment, thereby reducing the hardness and sodium storage space of the obtained carbon.
[0037] (4) The present invention combines deep oxidation treatment of the bulk phase of the thermosetting polymer with dehydration and cross-linking treatment of the aromatic structure, so that the carbonized carbon material has a Vickers hardness close to 2.0 GPa, thereby enabling it to maintain 80% of its capacity after 15,000 cycles, and its cycle performance is far superior to the current commercially available hard carbon negative electrode materials.
[0038] The preparation method provided by the present invention adopts specific process steps to achieve overall good interaction, which can solve the problems of low hardness and poor cycle performance of existing sodium battery hard carbon negative electrode materials; the proposal of the present invention will be of great significance to promoting the industrialization process of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic diagram of a plasma reaction device provided in Example 1 of the present invention;
[0040] Figure 2 This is a scanning electron microscope image of the high hardness carbon material provided in Example 1 of the present invention;
[0041] Figure 3 This is a transmission electron microscope image of the high hardness carbon material provided in Example 1 of the present invention;
[0042] Figure 4 The XRD spectrum of the high hardness carbon material provided in Example 1 of the present invention;
[0043] Figure 5 The Raman spectrum of the high hardness carbon material provided in Example 1 of the present invention;
[0044] Figure 6 A graph showing the relationship between the Vickers hardness value and the load of the high-hardness carbon material provided in Example 1 of the present invention;
[0045] Figure 7 The 0.1C charge-discharge curve of the high-hardness carbon negative electrode of the sodium ion battery provided in Example 1 of the present invention;
[0046] Figure 8 This is the 0.1C cycle curve of the high hardness carbon negative electrode of the sodium ion battery provided in Example 1 of the present invention.
[0047] The meanings of the various marks in the figure are: 1. discharge positive electrode; 2. vacuum device; 3. sealing device; 4. high-pressure reactor; 5. discharge negative electrode. DETAILED DESCRIPTION
[0048] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of this embodiment can be combined with each other. The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The present invention provides a method and device for enhancing the hardness of a carbon material and application thereof in a sodium ion battery, comprising the following steps:
[0050] S1, placing a thermosetting polymer in a reaction device including a high-pressure reactor and a low-temperature bath, and allowing the polymer to stand in a low-temperature, high-pressure environment in a pure oxygen atmosphere to obtain an oxygen-saturated thermosetting polymer;
[0051] S2, placing the device used in S1 in a plasma excitation chamber, applying a high-voltage and high-frequency electric field while pumping the device used in S1 into a low-pressure atmosphere to obtain an oxidized thermosetting polymer;
[0052] S3, taking the oxidized thermosetting polymer obtained in S2, placing it in a catalyst solution, soaking and drying it, pre-carbonizing it under a protective atmosphere, acid-washing it, washing it with water to remove impurities, and drying it;
[0053] S4, taking the pre-carbonized product obtained in S3, heating it for a second time for carbonization, and cooling it to obtain a high-hardness carbon material.
[0054] In the present invention, the thermosetting polymer is selected from one or more of phenolic resin, epoxy resin, unsaturated polyester resin, silicone resin, polyurethane, and urea-formaldehyde resin. Unsaturated polyester resin is more preferred, as the unsaturated bonds in such resins provide conditions for subsequently improving the degree of oxidation of the polymer. The particle size volume distribution of the thermosetting polymer is D 50 = 10 to 100 μm. More preferably, it is 30 to 50 μm. Too small a particle size will result in more carbon powder obtained by carbonization, resulting in a lower initial coulombic efficiency when storing sodium. Too large a particle size will result in incomplete oxidation of the polymer.
[0055] In the present invention, the device used in S1 includes a high-pressure reactor and a low-temperature bath, the thermosetting polymer is placed in the high-pressure reactor, the high-pressure reactor is filled with pure oxygen to high pressure and then sealed, the high-pressure reactor is placed in a low-temperature bath, and a low-temperature medium is placed in the low-temperature bath, and the low-temperature medium is selected from one or more of liquid oxygen, liquid nitrogen, liquid argon, liquid air, and liquid helium. Liquid helium is more preferred, because its temperature is relatively low, which can reduce the saturated vapor pressure of oxygen and allow oxygen to be more fully adsorbed in the bulk phase of the polymer.
[0056] In the present invention, the low temperature in S1 is -300 to -100°C, and more preferably -300 to -200°C. If the standing temperature is too low, it is difficult to reach with conventional low-temperature media, and if the standing temperature is too high, the saturated vapor pressure of oxygen will be too high, which is not conducive to oxygen adsorption by the polymer.
[0057] In the present invention, the high pressure in S1 is 100-1000 kPa, and more preferably 100-300 kPa. Too low a pressure will make the polymer unsaturated in oxygen adsorption, and too high a pressure will put forward higher requirements on the reaction device.
[0058] In the present invention, the standing time in S1 is 0.5-10 hours, and more preferably 1-3 hours. If the standing time is too short, the polymer will not be saturated with oxygen adsorption, and if the standing time is too long, the production efficiency will be reduced.
[0059] In the present invention, the device includes a low-temperature bath 6 and a high-pressure reactor 4 placed in the low-temperature bath 6, the low-temperature bath 6 is filled with a low-temperature medium, the high-pressure reactor 4 is sealed by a sealing device 3, and also includes a vacuum device 2 for regulating the pressure of the high-pressure reactor 4, and also includes a discharge positive electrode 1 and a discharge negative electrode 5. The discharge positive electrode 1 and the discharge negative electrode 5 are placed on both sides of the low-temperature bath 6 and the high-pressure reactor 4 as a whole, so that a plasma excitation chamber is formed between the low-temperature bath 6 and the high-pressure reactor 4.
[0060] In the present invention, the gas pressure of the plasma excitation chamber S2 is 0.001 to 1×10 -7 Pa, more preferably 1×10 -4 Below Pa, when the gas pressure is too high, the plasma temperature generated is high, which will cause oxygen desorption of oxygen-saturated polymers and easily cause equipment burning.
[0061] In the present invention, the voltage of the electric field in S2 is 1-100 kV, and the frequency is 1-10 GHz. More preferably, the voltage is above 10 kV, and the frequency is above 5 GHz. The high voltage and high frequency are for generating low-temperature oxygen plasma.
[0062] In the present invention, the device used in S1 described in S2 needs to be pumped to 0.001-1×10 -7Pa. If the vacuum pumping is turned on too early, a large amount of low-temperature medium will evaporate, the temperature of the reactor will rise, and the oxygen-saturated polymer will desorb oxygen. If the vacuum pumping is turned on too late, the gas pressure in the reactor will be too high, and the temperature of the generated plasma will be high, which will also cause the oxygen-saturated polymer to desorb oxygen and easily cause equipment burning.
[0063] In the present invention, the catalyst solution in S3 is selected from one or more of zinc chloride solution, calcium chloride solution, nickel chloride solution, and ferric chloride solution. More preferably, it is zinc chloride solution, which has the most significant dehydration effect on the polymer at the reaction temperature. The mass fraction of the catalyst solution is 5%-50%. More preferably, it is 30%-40%. If the concentration of the catalyst solution is too low, a larger reactor device will be required, and the energy consumption of the subsequent drying process will be increased. If the concentration of the catalyst solution is too high, the solution will be too viscous, which is not conducive to the diffusion of the catalyst into the bulk phase of the oxidized polymer.
[0064] In the present invention, the impregnation ratio of the catalyst in S3 to the oxidized thermosetting polymer is (0.1-5): 1. More preferably, it is (3-5): 1. If the impregnation ratio is too low, the degree of dehydration of the oxidized thermosetting polymer will be low, the hardness of the subsequently obtained carbon will be low, and the carbon yield will be low; if the impregnation ratio is too high, the specific surface area of the subsequently obtained carbon will be large, resulting in a lower coulombic efficiency when storing sodium.
[0065] In the present invention, the protective gas in S3 is selected from one or more of nitrogen, argon and helium, and is more preferably nitrogen.
[0066] In the present invention, the pre-carbonization temperature in S3 is 400-900°C, and the pre-carbonization time is 0.5-10h. The pre-carbonization temperature is preferably 500-600°C, and the pre-carbonization time is preferably 2-4h. Too low a temperature and too short a time cannot achieve the dehydration effect, so that the hardness of the subsequently obtained carbon is low; too high a temperature and too long a time both lead to an excessive degree of dehydration, resulting in more macropores, so that the specific surface area of the subsequently obtained carbon is larger, resulting in a lower coulombic efficiency when storing sodium.
[0067] In the present invention, the acid used for pickling in S3 is 0.1 mol / L to 1 mol / L hydrochloric acid, nitric acid or sulfuric acid. More preferably, it is 0.5 mol / L hydrochloric acid. If the concentration of the acid is too low, it is not enough to remove the ash and tar of the product; and if the concentration of the acid is too high, it will increase the subsequent waste liquid treatment cost. The degree of water washing needs to meet the filtrate pH value of 5-9. More preferably, it is 7, and the neutral filtrate indicates that the product impurities are completely removed.
[0068] In the present invention, the carbonization heating rate described in S4 is 1 to 10°C / min. More preferably, it is 5 to 10°C / min. Too slow a heating rate will increase production costs, and too fast a heating rate is not conducive to the full carbonization of the product. The carbonization temperature is 1000-1700°C, more preferably 1400-1600°C, and the carbonization time is 2-10h, more preferably 4-5h. If the carbonization temperature is too low or the carbonization time is too short, the carbonization degree of the obtained carbon is higher and the specific surface area is larger, resulting in a lower coulombic efficiency when storing sodium; if the carbonization temperature is too high or the carbonization time is too long, ineffective energy consumption will be increased.
[0069] In the present invention, the carbonization method described in S4 also includes introducing a hydrocarbon-containing gas at a flow rate of 0.1-1000ml / min during the reaction process for surface coating or pore plugging, more preferably 300-700ml / min. If the concentration of the hydrocarbon gas is too high, excessive ineffective deposited carbon will be introduced, reducing the sodium storage capacity and initial coulomb efficiency of the material. If the concentration of the hydrocarbon gas is too low, it will not be sufficient to play a coating role, increasing the specific surface area of the carbon obtained, resulting in a lower coulomb efficiency when storing sodium.
[0070] In the present invention, the hydrocarbon-containing gas includes any one or more of natural gas, methane, ethane, acetylene, propyne, benzene, toluene, and xylene, and more preferably benzene, which has a lower carbonization temperature and a faster carbonization rate.
[0071] The preparation method provided by the present invention adopts specific process steps to achieve better overall interaction; low-temperature oxygen adsorption is used to allow oxygen to enter the interior of the polymer precursor, and combined with oxygen plasma technology with strong oxidation, the polymer precursor can have a higher degree of oxidation. Combined with the dehydration effect of the catalyst, the aromatic structure in the polymer is fully cross-linked, so that the carbonized carbon material has a higher hardness. The hard carbon negative electrode prepared by the present invention has a Vickers hardness of 1.1 to 2.0 GPa, which makes it show excellent cycle performance, which is much higher than the current commercially available hard carbon negative electrode.
[0072] The present invention provides a method for enhancing the hardness of a carbon material and application thereof in a sodium ion battery, which has the following beneficial effects:
[0073] (1) The present invention hardens the intrinsic structure of the hard carbon active material without introducing inactive components, thus having a higher sodium storage capacity.
[0074] (2) The present invention combines bulk adsorption of oxygen under low temperature conditions with low temperature oxygen plasma technology to deeply oxidize the bulk phase of the precursor, thereby overcoming the shortcoming that conventional plasma technology can only perform surface oxidation treatment.
[0075] (3) The present invention introduces a catalyst to dehydrate the precursor, so that the aromatic structure of the precursor is fully cross-linked, thereby preventing the carbon layer from stacking during the subsequent heat treatment, thereby reducing the hardness and sodium storage space of the obtained carbon.
[0076] (4) The present invention combines deep oxidation treatment of the bulk phase of the thermosetting polymer with dehydration and cross-linking treatment of the aromatic structure, so that the carbonized carbon material has a Vickers hardness close to 2.0 GPa, thereby enabling it to maintain 80% of its capacity after 15,000 cycles, and its cycle performance is far superior to the current commercially available hard carbon negative electrode materials.
[0077] The invention will be of great significance in promoting the application of sodium ion batteries in the field of energy storage.
[0078] In order to further illustrate the present invention, the following examples are provided for detailed description. In the following examples of the present invention, if no specific conditions are specified, the reaction is carried out according to conventional conditions or conditions recommended by the manufacturer, and if no manufacturer is specified for the reagents or instruments used, all of them are conventional products that can be purchased commercially.
[0079] Example 1
[0080] (1) 1 g of unsaturated polyester resin is placed in a high-pressure reactor, the reactor is filled with pure oxygen to 150 kPa and then sealed, the high-pressure reactor is placed in a low-temperature bath containing liquid helium, the reactor temperature reaches -269°C, and after standing for 3 hours, an oxygen-saturated thermosetting polymer is obtained;
[0081] (2) The high-pressure reactor and the low-temperature bath are transferred to the plasma excitation chamber, and the high-pressure reactor is connected to a vacuum device. The reaction device is as follows: Figure 1 As shown. A 70 kV, 10 GHz electric field was applied, and the high-pressure reactor and plasma excitation chamber were simultaneously evacuated to a vacuum of 1×10 -6 Pa, and an oxidative thermosetting polymer was obtained after 1 h of reaction.
[0082] (3) The oxidized thermosetting polymer is placed in 7.5 g of a 40% zinc chloride solution, where the impregnation ratio of zinc chloride to polymer is 3:1. After standing for 24 hours, it is dried in an oven until the moisture is completely removed. It is then heated to 600°C in a nitrogen atmosphere and pre-carbonized for 3 hours. After cooling, it is placed in 0.5 mol / L hydrochloric acid and stirred for washing for 24 hours. It is then filtered repeatedly with pure water until the filtrate has a pH of 7 to obtain a pre-carbonized product.
[0083] (4) The pre-carbonized product was heated to 1600°C at a rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 4 hours. During this period, 300 ml / min of benzene was introduced in the last 20 minutes. After cooling, a high-hardness carbon material was obtained.
[0084] The high hardness carbon material prepared in Example 1 was characterized by using a Dutch Phenom field emission scanning electron microscope (SEM). Figure 2 As shown by Figure 2 It can be seen that the prepared hard carbon has an irregular block shape and its surface is smooth.
[0085] The high hardness carbon material prepared in Example 1 was characterized using a Thermo Fisher transmission electron microscope Talos F200i (TEM). Figure 3 As shown by Figure 3 It can be seen that the prepared hard carbon has almost no layered structure and the degree of cross-linking of microcrystals is high.
[0086] The high hardness carbon material prepared in Example 1 was characterized by using a Japanese Rigaku X-ray diffractometer Smartlab (XRD). Figure 4 As shown by Figure 4 It can be seen that the (002) peak of the prepared hard carbon almost disappears, indicating the lack of a layered structure.
[0087] The high hardness carbon material prepared in Example 1 was characterized by using the Japanese Horiba confocal Raman spectrometer LabRAM (Raman). Figure 5 As shown by Figure 5 It can be seen that the D peak of the prepared hard carbon is strong and broad, indicating that its defect structure is rich.
[0088] The high hardness carbon material prepared in Example 1 was characterized using Shanghai Yizong HV-1000 (Vickers hardness tester). The results are as follows: Figure 6 As shown by Figure 6 It can be seen that the convergence value of the hardness of the prepared hard carbon under a load of 20N is 2GPa.
[0089] The hard carbon negative electrode material prepared in Example 1 was mixed with conductive carbon powder and CMC and SBR binders in a mass ratio of 93.7:2.5:1.8:2, and then coated on an aluminum foil after homogenization. After drying at 70°C, it was rolled with a double-roller machine, and then a pole piece with a diameter of 10 mm was obtained by a punching machine. The weight was weighed and the mass of the aluminum foil was deducted to obtain the mass of the active substance.
[0090] After drying the negative electrode sheet, CR2032 button half-cells were assembled in an inert gas glove box in Mikaelona, Germany. They were assembled in the order of negative electrode shell, negative electrode sheet, electrolyte, diaphragm, electrolyte, sodium sheet, gasket, shrapnel, and positive electrode shell. The electrochemical performance of CR2032 button half-cells was tested using the Xinwei battery test system, with a voltage range of 0V to 2.5V. Figure 7 This is the 0.1C charge and discharge curve. Figure 8The 0.1C cycle curve shows that the prepared hard carbon has a specific capacity of 380 mAh / g and still has a capacity retention rate of 80% after 15,000 cycles.
[0091] Example 2
[0092] The preparation method provided in Example 1 was adopted, except that in step (1), 1 g of phenolic resin was placed in a high-pressure reactor.
[0093] Example 3
[0094] The preparation method provided in Example 1 was adopted, with the only difference being that in step (1), the autoclave was filled with pure oxygen to 100 kPa and then sealed.
[0095] Example 4
[0096] The preparation method provided in Example 1 was used, with the only difference being that in step (1), the high-pressure reactor was placed in a low-temperature bath containing liquid nitrogen, and the temperature of the reactor reached -147°C.
[0097] Example 5
[0098] The preparation method provided in Example 1 was adopted, except that an electric field of 50 kV and 5 GHz was applied.
[0099] Example 6
[0100] The preparation method provided in Example 1 was used, except that the high pressure reaction kettle and the plasma excitation chamber were evacuated to a vacuum of 1×10 -4 Pa.
[0101] Example 7
[0102] The preparation method provided in Example 1 was adopted, except that the oxidative thermosetting polymer was placed in 60 g of 5% zinc chloride solution.
[0103] Example 8
[0104] The preparation method provided in Example 1 was adopted, except that the oxidized thermosetting polymer was placed in 7.5 g of 40% nickel chloride solution.
[0105] Example 9
[0106] The preparation method provided in Example 1 was used, except that the oxidative thermosetting polymer was placed in 2.5 g of a 40% zinc chloride solution, and the impregnation ratio of zinc chloride to polymer was 1:1.
[0107] Example 10
[0108] The preparation method provided in Example 1 was adopted, with the only difference being that the pre-carbonization procedure was to heat the material to 500° C. in an argon atmosphere and pre-carbonize the material for 4 h.
[0109] Embodiment 11
[0110] The preparation method provided in Example 1 was used, except that the carbonization procedure was to heat the pre-carbonized product to 1400° C. at a rate of 5° C. / min under a nitrogen atmosphere and keep the temperature for 5 h.
[0111] Example 12
[0112] The preparation method provided in Example 1 was adopted, except that 300 ml / min of methane was introduced in the last 20 min of the carbonization process.
[0113] Comparative Example 1
[0114] (1) Place 1 g of unsaturated polyester resin in a high-pressure reactor, fill the reactor with pure oxygen to 150 kPa, seal it, and let it stand for 3 hours.
[0115] (2) The high-pressure reactor was placed in a plasma excitation chamber. A vacuum device was connected to the high-pressure reactor. An electric field of 70 kV and 10 GHz was applied. At the same time, the high-pressure reactor and the plasma excitation chamber were evacuated to a vacuum of 1×10 -6 Pa, and an oxidative thermosetting polymer was obtained after 1 h of reaction.
[0116] (3) The oxidized thermosetting polymer is placed in 7.5 g of a 40% zinc chloride solution, where the impregnation ratio of zinc chloride to polymer is 3:1. After standing for 24 hours, it is dried in an oven until the moisture is completely removed. It is then heated to 600°C in a nitrogen atmosphere and pre-carbonized for 3 hours. After cooling, it is placed in 0.5 mol / L hydrochloric acid and stirred for washing for 24 hours. It is then filtered repeatedly with pure water until the filtrate has a pH of 7 to obtain a pre-carbonized product.
[0117] (4) The pre-carbonized product was heated to 1600°C at a rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 4 hours. During this period, 300 ml / min of benzene was introduced in the last 20 minutes. After cooling, the carbon material was obtained.
[0118] Comparative Example 2
[0119] (1) 1 g of unsaturated polyester resin is placed in 7.5 g of 40% zinc chloride solution, where the impregnation ratio of zinc chloride to polymer is 3:1. After standing for 24 hours, it is dried in an oven until the moisture is completely removed. Then, the temperature is raised to 600°C in a nitrogen atmosphere, and pre-carbonized for 3 hours. After cooling, it is placed in 0.5 mol / L hydrochloric acid and stirred for washing for 24 hours. Then, it is repeatedly filtered with pure water until the filtrate has a pH of 7 to obtain a pre-carbonized product.
[0120] (2) The pre-carbonized product was heated to 1600°C at a rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 4 hours. During this period, 300 ml / min of benzene was introduced in the last 20 minutes. After cooling, the carbon material was obtained.
[0121] Comparative Example 3
[0122] 1 g of unsaturated polyester resin was heated to 1600° C. at a rate of 5° C. / min under a nitrogen atmosphere and kept at that temperature for 4 h. During this period, 300 ml / min of benzene was introduced in the last 20 min. After cooling, a carbon material was obtained.
[0123] Comparative Example 4
[0124] The preparation method provided in Example 1 was adopted, with the only difference being that in step (1), 1 g of asphalt was placed in a high-pressure reactor.
[0125] Comparative Example 5
[0126] The preparation method provided in Example 1 was used, with the only difference being that in step (1), the kettle was filled with pure oxygen to 50 kPa and then sealed.
[0127] Comparative Example 6
[0128] The preparation method provided in Example 1 was used, with the only difference being that an electric field of 100 V and 0.1 GHz was applied.
[0129] Comparative Example 7
[0130] The preparation method provided in Example 1 was adopted, with the only difference being that the high-pressure reaction vessel and the plasma excitation chamber were evacuated to a vacuum of 0.01 Pa.
[0131] Comparative Example 8
[0132] The preparation method provided in Example 1 was used, except that: after applying an electric field of 70 kV and 10 GHz, the high-pressure reactor and the plasma excitation chamber were evacuated to a vacuum of 1×10 -6 Pa.
[0133] Comparative Example 9
[0134] (1) 1 g of unsaturated polyester resin is placed in a high-pressure reactor, the reactor is filled with pure oxygen to 150 kPa and then sealed, the high-pressure reactor is placed in a low-temperature bath containing liquid helium, the reactor temperature reaches -269°C, and after standing for 3 hours, an oxygen-saturated thermosetting polymer is obtained;
[0135] (2) The high-pressure reactor and the low-temperature bath are transferred to the plasma excitation chamber, and the high-pressure reactor is connected to a vacuum device. The reaction device is as follows: Figure 1 As shown. A 70 kV, 10 GHz electric field was applied, and the high-pressure reactor and plasma excitation chamber were simultaneously evacuated to a vacuum of 1×10-6 Pa, and an oxidative thermosetting polymer was obtained after 1 h of reaction.
[0136] (3) The oxidized thermosetting polymer is heated to 600° C. in a nitrogen atmosphere, pre-carbonized for 3 h, cooled, placed in 0.5 mol / L hydrochloric acid, stirred and washed for 24 h, and then repeatedly filtered with pure water until the filtrate has a pH of 7 to obtain a pre-carbonized product.
[0137] (4) The pre-carbonized product was heated to 1600°C at a rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 4 hours. During this period, 300 ml / min of benzene was introduced in the last 20 minutes. After cooling, the carbon material was obtained.
[0138] Comparative Example 10
[0139] The preparation method provided in Example 1 was adopted, except that the oxidative thermosetting polymer was placed in 4.3 g of 70% zinc chloride solution.
[0140] Comparative Example 11
[0141] The preparation method provided in Example 1 was used, except that the oxidative thermosetting polymer was placed in 25 g of a 40% zinc chloride solution, and the impregnation ratio of zinc chloride to polymer was 10:1.
[0142] Comparative Example 12
[0143] The preparation method provided in Example 1 was adopted, except that the pre-carbonization procedure was to raise the temperature to 800° C. in a nitrogen atmosphere and pre-carbonize for 2 h.
[0144] Comparative Example 13
[0145] The preparation method provided in Example 1 was adopted, except that the pre-carbonization procedure was to raise the temperature to 600° C. in a nitrogen atmosphere and pre-carbonize for 12 h.
[0146] Comparative Example 14
[0147] The preparation method provided in Example 1 was adopted, except that the carbonization procedure was to heat the pre-carbonized product to 900° C. at a rate of 5° C. / min under a nitrogen atmosphere and keep the temperature for 4 h.
[0148] Comparative Example 15
[0149] The preparation method provided in Example 1 is adopted, except that no hydrocarbon gas is introduced during the carbonization process.
[0150] Comparative Example 16
[0151] The preparation method provided in Example 1 was adopted, except that 2000 ml / min of benzene was introduced in the last 20 min of the carbonization procedure.
[0152] Comparative Example 17
[0153] Commercially available hard carbon anode for sodium-ion batteries.
[0154] Performance Testing
[0155] The hard carbon negative electrode material for sodium ion batteries in each embodiment and comparative example was mixed with conductive carbon powder and CMC and SBR binders in a mass ratio of 93.7:2.5:1.8:2, and then coated on an aluminum foil sheet after homogenization. After drying at 70°C, the sheet was rolled with a double-roller machine, and then a pole sheet with a diameter of 10 mm was obtained by a punching machine. The weight was weighed and the mass of the aluminum foil was deducted to obtain the mass of the active substance.
[0156] After drying the negative electrode sheet, the CR2032 button half-cell was assembled in the inert gas glove box of Mikaelona, Germany. The negative electrode shell, negative electrode sheet, electrolyte, diaphragm, electrolyte, sodium sheet, gasket, spring, and positive electrode shell were assembled in this order. The electrochemical performance of the CR2032 button half-cell was tested using the Xinwei battery test system with a voltage range of 0V to 2.5V. The test results are shown in Table 1.
[0157] The effect data of the performance test is shown in Table 1 below.
[0158] Table 1 Effect data table
[0159]
[0160]
[0161] It can be seen from Example 1 and Comparative Example 17 in Table 1 that the deep oxidation effect of the polymer can be achieved by adsorbing oxygen in the bulk phase of the thermosetting polymer and combining the oxygen plasma technology. Combined with the subsequent catalyst dehydration and heat treatment, the prepared carbon material has a higher hardness and exhibits excellent cycle performance compared to commercially available hard carbon.
[0162] It can be seen from Comparative Example 1 that adsorption in a low temperature environment before plasma treatment plays an important role. Skipping the adsorption step will cause plasma oxidation to occur only on the surface, resulting in a lower hardness of the product.
[0163] It can be seen from Comparative Examples 2 and 3 that plasma treatment is the key to increasing the oxygen content of the precursor and enhancing the hardness of the obtained carbon. Simple heat treatment of the polymer precursor cannot make the carbonized material have sufficient hardness.
[0164] It can be seen from Comparative Example 4 that the selection of the precursor plays an important role in the hardness of the produced carbon;
[0165] It can be seen from Comparative Example 5 that if the pressure is low during low-temperature adsorption, the polymer will not be able to reach oxygen saturation, which will affect the hardness of the produced carbon;
[0166] From Comparative Examples 6, 7, and 8, it can be seen that during the plasma treatment process, a high-voltage and high-frequency electric field, a low-pressure atmosphere, and a vacuum device must be turned on in time at the beginning of the plasma treatment, otherwise the temperature in the reactor will increase, causing oxygen desorption in the polymer;
[0167] It can be seen from Comparative Example 9 that the dehydration step of the catalyst can fully cross-link the aromatic structure in the precursor. Skipping the dehydration step will lead to a close arrangement of the carbon layer during the subsequent heat treatment, loss of sodium storage sites and reduced material hardness, resulting in poor sodium storage capacity and cycle stability.
[0168] It can be seen from Comparative Example 10 that the concentration of the catalyst solution needs to be controlled in an appropriate range. If the concentration is too high, it will be difficult for the catalyst to diffuse into the precursor bulk phase, thereby affecting the dehydration effect.
[0169] From Comparative Examples 11, 12, and 13, it can be seen that a suitable impregnation ratio of the catalyst to the precursor and a low-temperature, short-time heat treatment procedure are important conditions for preventing excessive dehydration of the catalyst. Excessive dehydration will increase the specific surface area of the carbon produced, affecting the coulombic efficiency and cycle performance during sodium storage.
[0170] It can be seen from Comparative Example 14 that the temperature of the second heat treatment needs to be controlled within a relatively high range, otherwise the pores of the produced carbon will not be sufficiently closed, thereby resulting in an increase in the specific surface area;
[0171] It can be seen from Comparative Examples 15 and 16 that the coating process can further reduce the specific surface area of the produced carbon, but the flow rate of the hydrocarbon gas needs to be controlled. If the flow rate is too high, too much invalid carbon deposits will be generated, which will increase the specific surface area of the produced carbon and result in poor cycle performance.
[0172] The preparation method provided by the present invention adopts specific steps, conditions and parameters to achieve overall good interaction. The prepared product has a sodium storage capacity of 380 mAh / g and a cycle stability of 15,000 cycles, and its comprehensive performance is better than that of commercially available hard carbon.
[0173] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
[0174] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for increasing the hardness of a carbon material, characterized in that: The following steps are involved: S1. placing a thermosetting polymer in a reaction device and allowing it to stand in a pure oxygen atmosphere at a low temperature and high pressure to obtain an oxygen-saturated thermosetting polymer; the low temperature in S1 is -300 to -100° C.; the high pressure in S1 is 100 to 1000 kPa; S2, placing the reaction device used in S1 in a plasma excitation chamber, applying a high-voltage and high-frequency electric field while pumping the reaction device used in S1 into a low-pressure atmosphere to obtain an oxidized thermosetting polymer; S3, taking the oxidized thermosetting polymer obtained in S2 and placing it in a catalyst solution, soaking and drying, pre-carbonizing under a protective atmosphere, acid washing and water washing to remove impurities and drying; the catalyst solution in S3 is selected from one or more of zinc chloride solution, calcium chloride solution, nickel chloride solution, and ferric chloride solution, and the mass fraction of the catalyst solution is 5%-50%; S4, taking the pre-carbonized product obtained in S3, heating it for a second time for carbonization, and cooling it to obtain a high-hardness carbon material.
2. The method for enhancing the hardness of a carbon material according to claim 1, characterized in that: S1 The thermosetting polymer is selected from one or more of phenolic resin, epoxy resin, unsaturated polyester resin, silicone resin, polyurethane, and urea-formaldehyde resin; the particle size volume distribution of the thermosetting polymer is D 50 =10~100μm.
3. The method for enhancing the hardness of a carbon material according to claim 1, characterized in that: The reaction device used in S1 includes a high-pressure reactor and a low-temperature bath. The thermosetting polymer is placed in the high-pressure reactor. The high-pressure reactor is filled with pure oxygen to a high pressure and then sealed. The high-pressure reactor is placed in a low-temperature bath. A low-temperature medium is placed in the low-temperature bath. The low-temperature medium is selected from one or more of liquid oxygen, liquid nitrogen, liquid argon, liquid air, and liquid helium.
4. The method for enhancing the hardness of a carbon material according to claim 1, characterized in that: The standing time in S1 is 0.5-10h.
5. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The gas pressure of the plasma excitation chamber is 0.001~1×10 -7 Pa.
6. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The voltage of the electric field S2 is 1~100kV, and the frequency is 1~10GHz.
7. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: S2 medium and low pressure atmosphere is pumped to 0.001~1×10 -7 Pa.
8. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The impregnation ratio of the catalyst to the oxidative thermosetting polymer in S3 is 0.1~5:
1.
9. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: S3 The protective gas is selected from one or more of nitrogen, argon and helium.
10. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The pre-carbonization temperature in S3 is 400-900°C, and the pre-carbonization time is 0.5-10h.
11. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The acid used for pickling in S3 is 0.1 mol / L to 1 mol / L hydrochloric acid, nitric acid or sulfuric acid, and the degree of water washing needs to satisfy the pH value of the filtrate of 5-9.
12. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: The carbonization heating rate in S4 is 1-10°C / min, the carbonization temperature is 1000-1700°C, and the carbonization time is 2-10h.
13. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: S4 The carbonization method further comprises: During the reaction process of step S4, a hydrocarbon-containing gas is introduced at a flow rate of 0.1-1000 ml / min for surface coating or pore plugging; The hydrocarbon-containing gas includes any one or more of natural gas, methane, ethane, acetylene, propyne, benzene, toluene and xylene.
14. The method for increasing the hardness of a carbon material according to claim 1, characterized in that: S4 The high hardness carbon material has a Vickers hardness of 1.1~2.0 GPa.
15. A device for increasing the hardness of a carbon material, used to implement the method for increasing the hardness of a carbon material according to any one of claims 1 to 14, characterized in that: The invention comprises a low-temperature bath (6) and a high-pressure reactor (4) placed in the low-temperature bath (6), wherein the low-temperature bath (6) contains a low-temperature medium, the high-pressure reactor (4) is sealed by a sealing device (3), and further comprises a vacuum device (2) for regulating the pressure of the high-pressure reactor (4), and further comprises a discharge positive electrode (1) and a discharge negative electrode (5), wherein the discharge positive electrode (1) and the discharge negative electrode (5) are placed on both sides of the low-temperature bath (6) and the high-pressure reactor (4) as a whole, so that a plasma excitation chamber is formed between the low-temperature bath (6) and the high-pressure reactor (4).
16. Use of the high hardness carbon material according to any one of claims 1 to 14 in the field of negative electrodes of sodium ion batteries.